A facile synthesis of functionalized 7,8-diaza[5]helicenes through an oxidative ring-closure of 1,1’-binaphthalene-2,2’-diamines (BINAMs) - Takeda, Youhei; Okazaki, Masato; Maruoka, Yoshiaki; Minakata, Satoshi (Beilstein Journal of Organic Chemistry, 2015)
A facile and moderately functional-group-tolerant synthetic method for the preparation of 7,8-diaza[5]helicenes has been developed. It comprises of an oxidative ring-closing process of 1,1’-binaphthalene-2,2’-diamine (BINAM) derivatives with a chlorine-containing oxidant (t-BuOCl) in the presence of a base (2,6-lutidine). In addition the basic physicochemical properties of newly synthesized compounds have been investigated.
Keywords: aromatic amines; azahelicenes; cinnolines; halogen; oxidation

(untitled) - Meisenheimer, J.; Witte, K. (Ber. Dtsch. Chem. Ges., 1903)

(untitled) - Martin, R. H. (Angew. Chem., 1974)
Angew. Chem., Int. Ed. Engl. 1974, 13, 649–660. doi:10.1002/anie.197406491

(untitled) - Urbano, A. (Angew. Chem., 2003)
Angew. Chem., Int. Ed. 2003, 42, 3986–3989. doi:10.1002/anie.200301667

(untitled) - Collins, S. K.; Vachon, M. P. (Org. Biomol. Chem., 2006)

(untitled) - Dumitrascu, F.; Dumitrescu, D. G.; Aron, I. (ARKIVOC, 2010)

(untitled) - Shen, Y.; Chen, C.-F. (Chem. Rev., 2012)

(untitled) - Gingras, M. (Chem. Soc. Rev., 2012)

(untitled) - Gingras, M.; Félix, G.; Peresutti, R. (Chem. Soc. Rev., 2013)

(untitled) - Gingras, M. (Chem. Soc. Rev., 2012)

(untitled) - Aillard, P.; Voituriez, A.; Marinetti, A. (Dalton Trans., 2014)

(untitled) - Saleh, N.; Shen, C.; Crassous, J. (Chem. Sci., 2014)

(untitled) - Corbett, J. F.; Holt, P. F.; Hughes, A. N. (J. Chem. Soc., 1961)

(untitled) - Li, W.; Cai, X.; Hu, Y.; Ye, Y.; Luo, M.; Hu, J. (J. Mol. Struct.: THEOCHEM, 2005)

(untitled) - Caronna, T.; Castiglione, F.; Famulari, A.; Fontana, F.; Malpezzi, L.; Mele, A.; Mendola, D.; Sora, I. N. (Molecules, 2012)

(untitled) - Porter, J. J.; Murray, J. L. (J. Am. Chem. Soc., 1965)

(untitled) - Ellgen, P. C.; McMullin, S. L. (Inorg. Chem., 1973)

(untitled) - Nixon, J. F.; Kooti, M. (J. Organomet. Chem., 1978)

(untitled) - Cumming, W. M.; Ferrier, G. S. (J. Chem. Soc., 1924)

(untitled) - Bellaart, A. C. (Tetrahedron, 1965)

(untitled) - Braithwaite, R. S. W.; Holt, P. F. (J. Chem. Soc., 1959)

(untitled) - Corbett, J. F.; Holt, P. F. (J. Chem. Soc., 1960)

(untitled) - Holt, P. F.; Went, C. W. (J. Chem. Soc., 1963)

(untitled) - Corbett, J. F.; Holt, P. F. (J. Chem. Soc., 1961)

(untitled) - Caronna, T.; Fontana, F.; Mele, A.; Sora, I. N.; Panzeri, W.; Viganò, L. (Synthesis, 2008)

(untitled) - De, C. K.; Pesciaioli, F.; List, B. (Angew. Chem., 2013)
Angew. Chem., Int. Ed. 2013, 52, 9293–9295. doi:10.1002/anie.201304039

(untitled) - Li, G.-Q.; Gao, H.; Keene, C.; Devonas, M.; Ess, D. H.; Kürti, L. (J. Am. Chem. Soc., 2013)

(untitled) - Takeda, Y.; Okumura, S.; Minakata, S. (Angew. Chem., 2012)
Angew. Chem., Int. Ed. 2012, 51, 7804–7808. doi:10.1002/anie.201202786

(untitled) - Takeda, Y.; Okumura, S.; Minakata, S. (Synthesis, 2013)

(untitled) - Okumura, S.; Takeda, Y.; Kiyokawa, K.; Minakata, S. (Chem. Commun., 2013)

(untitled) - Okumura, S.; Lin, C.-H.; Takeda, Y.; Minakata, S. (J. Org. Chem., 2013)

(untitled) - Takeda, Y.; Okazaki, M.; Minakata, S. (Chem. Commun., 2014)

(untitled) - Benoit, R. L.; Lefebvre, D.; Fréchette, M. (Can. J. Chem., 1987)

(untitled) - Leffek, K. T.; Pruszynski, P.; Thanapaalasingham, K. (Can. J. Chem., 1989)

(untitled) - Andon, R. J. L.; Cox, J. D.; Herington, E. F. G. (Trans. Faraday Soc., 1954)

(untitled) - Burrows, P. E.; Shen, Z.; Bulovic, V.; McCarty, D. M.; Forrest, S. R.; Cronin, J. A.; Thompson, M. E. (J. Appl. Phys., 1996)